2019
DOI: 10.3389/fnagi.2019.00124
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Netrin-1 and Correlated Th17/Tregs Balance Disorder in Aβ1–42 Induced Alzheimer’s Disease Model Rats

Abstract: There is increasing evidence indicating that inflammation represents a key pathological component of Alzheimer’s disease (AD). A possible factor that may contribute to this process is netrin-1, a neuronal guidance molecule. This molecule has been shown to exert an unexpected immunomodulatory function. However, the potential changes and correlations of netrin-1 with T helper 17/regulatory T cells (Th17/Tregs) as related to inflammation in AD has yet to be examined. In this study, netrin-1 and Th17/Tregs balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…Early studies found that NTN-1 interacts with the UNC-5B receptor expressed on the surface of the white blood cells and inhibits the migration of the white blood cells (Ly et al, 2005). In Alzheimer's disease (AD) rats (Sun et al, 2019), it has been demonstrated that NTN-1 concentrations in serum were positively correlated with the systemic expression of IL-10 (Mosser and Zhang, 2008). Moreover, in acute peritonitis and acute colitis models, NTN-1 inhibits the migration of inflammatory cells and induces the M2 polarization phenotype of macrophages (Mirakaj et al, 2011;Aherne et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that NTN-1 interacts with the UNC-5B receptor expressed on the surface of the white blood cells and inhibits the migration of the white blood cells (Ly et al, 2005). In Alzheimer's disease (AD) rats (Sun et al, 2019), it has been demonstrated that NTN-1 concentrations in serum were positively correlated with the systemic expression of IL-10 (Mosser and Zhang, 2008). Moreover, in acute peritonitis and acute colitis models, NTN-1 inhibits the migration of inflammatory cells and induces the M2 polarization phenotype of macrophages (Mirakaj et al, 2011;Aherne et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that NTN-1 interacts with the UNC-5B receptor expressed on the surface of white blood cells and inhibits the migration of white blood cells [19]. In Alzheimer's disease (AD) rats [51], it has been demonstrated that NTN-1 concentrations in the serum were positively correlated with the systemic expression of IL-10, one of the most important mediators in the anti-in ammatory activity [52]. What is more, in acute peritonitis and acute colitis models, NTN-1 inhibits the migration of in ammatory cells and induces the M2 polarization phenotype of macrophages [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The knock-down of Netrin-1 increased the level of Aβ in AD model mice, while the over-expression of Netrin-1 decreased its level, revealing that Netrin-1 had a protective role against Aβ [175]. It was also recently found that the level of Netrin-1 was decreased in both the serum and cerebrospinal fluid of an Aβ 1-42 -induced AD model rat, which further showed the association of Netrin-1 to the progression of AD [176]. Some scientists further demonstrated that treatment with Netrin-1 improved cognition in AD model mice [171,172].…”
Section: The Protective Role Of Netrin-1 Against Alzheimer's Diseasementioning
confidence: 80%